Psycholinguistic Explanation in Lexical Acquisition of Second Language (L2) Adult Learners - azman, ahmad (Pascasarjana Universitas HKBP Nommensen, 2024)
This paper is organized into several sections. First, a model of L2 lexical development is outlined. It starts with a review on the internal structure of the lexical entries in the mental lexicon. Then a comparison is made between the different conditions under which L2 and L1 are learned. The consequences of such differences for L2 lexical development and representation are thus highlighted. Finally, the three stages of L2 vocabulary acquisition on the basis of what is represented in the lexical entry are applied. Keywords : Lexical Aquisition , Second Language aquisition